Ict and social networks as tools for the dissemination of linkage with society: case of the university of Guayaquil - Samaniego Torres, Carlos Alberto; Pazmiño Vera, Marjorie Italia; Murillo Párraga, María Viviana; Contreras León, Narcisa Pilar (Conexiones UG, 2024)
This research analyzes the role of ICT and communication barriers in the teaching-learning processes of students with hearing and visual disabilities at the University of Guayaquil and how these can have a positive and negative impact on students and teachers. To achieve educational inclusion, it is necessary to work not only as a team but also in the domain of social constructivism, cognitivism and connectivism. Mixed methodology research, with a non-probabilistic sample, obtains conclusive data regarding the field of lack of teacher training and updating, lack of spaces and technological infrastructures, as well as a substantial change in the largest university in Ecuador. As a result, the construction of a web page is proposed that helps with various alternatives to overcome the walls and build a comprehensive EDERDI education.
Keywords: Learning; teaching; inclusion; ICT